2015
DOI: 10.18805/lr.v38i6.6729
|View full text |Cite
|
Sign up to set email alerts
|

Growth, yield attributes and yield of medium duration pigeonpea hybrid ICPH-2671 as influenced by fertility levels and planting geometry

Abstract: A field experiment was conducted during <italic>Kharif</italic> season 2009 to study the response of hybrid pigeonpea to planting geometry and fertility levels. The results revealed that the hybrid pigeonpea ICPH-2671 recorded significantly higher grain yield (2.40 tha<sup>−1</sup>) as compared to cv. Maruti (1.68 t ha<sup>−1</sup>) and the magnitude of increase was 41.7 % higher. The yield parameters like grain weight plant<sup>−1</sup>, number of pods plant<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
6
1
1
Order By: Relevance
“…The amount of phosphorus fertilizer applied did not have any significant effect on the drybean grain yield. The results of this study contradicted the findings by Meena et al (2015) who reported that the fertility level of 100 P kg/ha resulted in higher grain yield as compared to lower fertility level of 50 P kg/ha. The interactions of treatment factors had no significant effect (P>0.05) on drybean grain yield.…”
Section: Grain Yield (Kg/ha -1 )contrasting
confidence: 99%
“…The amount of phosphorus fertilizer applied did not have any significant effect on the drybean grain yield. The results of this study contradicted the findings by Meena et al (2015) who reported that the fertility level of 100 P kg/ha resulted in higher grain yield as compared to lower fertility level of 50 P kg/ha. The interactions of treatment factors had no significant effect (P>0.05) on drybean grain yield.…”
Section: Grain Yield (Kg/ha -1 )contrasting
confidence: 99%
“…The results are in agreement with the findings of Meena et al, (2015) and Waghmare et al, (2016). Highest seed yield (4330 kg/ha) were recorded in silver plastic mulch as compared to black plastic mulch (3948 kg/ha), drip irrigation (2356 kg/ha) and flood irrigation (889 kg/ha).…”
Section: Yield Parameterssupporting
confidence: 93%
“…The better availability of growth resources like water, nutrients, air, mulching, better cultural practices and effective weed control in mulch helped the plants to exhibit their full potential and produced higher yield than open field condition. The results are in agreement with the findings of Meena et al, (2015), Waghmare et al, (2016) and Gajera et al, (2002). Higher stalk yield were recorded in silver plastic mulch (9932 kg/ha) as compared to black plastic mulch (9874 kg/ha) and drip irrigation (5217 kg/ha) and lowest stalk yield recorded in flood irrigation condition (3652 kg/ha).…”
Section: Yield Parameterssupporting
confidence: 93%
“…Similar observations were made by Meena et al, (2015) who reported that higher grain yield with ICPH2671 was due to significantly higher number of pods per plant (181.2) pod weight per plant (117.9 g), grain weight per plant (63.1 g), test weight (10.2 g) and harvest index (25%) over Maruti (139.9, 65.3 g, 33.7 g, 9.2 g and 19%, respectively).…”
Section: Productivity and Economics Of Pigeonpea Genotypes As Influensupporting
confidence: 89%